2013
DOI: 10.1002/adma.201204097
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Memory States in Resistive Switching Devices Through Controlled Size and Orientation of the Conductive Filament

Abstract: Multilevel operation in resistive switching memory (RRAM) based on HfOx is demonstrated through variable sizes and orientations of the conductive filament. Memory states with the same resistance, but opposite orientation of defects, display a different response to an applied read voltage, therefore allowing an improvement of the information stored in each physical cell. The multilevel scheme allows a 50% increase (from 2 to 3 bits) of the stored information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 24 publications
2
136
0
1
Order By: Relevance
“…[1][2][3] More detailed mechanisms of transitions between low and high resistance states have also been discussed. [9][10][11] For example, Tsuruoka et al 9 measured voltage-current curves in a wide temperature range and suggested that the SET process can be understood from the inhomogeneous nucleation and subsequent growth of Cu filament while the RESET process can be attributed to Jouleheating-assisted dissolution. However, such previous analyses are based on classical, macroscopic theories, and thus the atomistic details of the mechanism are not necessarily well understood.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] More detailed mechanisms of transitions between low and high resistance states have also been discussed. [9][10][11] For example, Tsuruoka et al 9 measured voltage-current curves in a wide temperature range and suggested that the SET process can be understood from the inhomogeneous nucleation and subsequent growth of Cu filament while the RESET process can be attributed to Jouleheating-assisted dissolution. However, such previous analyses are based on classical, macroscopic theories, and thus the atomistic details of the mechanism are not necessarily well understood.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 This issue will be further exacerbate when the selected cell is in the high resistance state (HRS), whereas all unselected cells are in the low resistance state (LRS). In order to solve above issue, five methods have been proposed, including one transistor-one resistor structure (1T1R), 6,7 one diode-one resistor structure (1D1R), 8,9 one bidirectional selector-one resistor structure (1S1R), 10,11 complementary resistive switch (CRS), [12][13][14][15] and one resistor with self-rectifying effect. [16][17][18][19] Given the facts that integrating additional nonlinear access devices can inevitably increase the complexity of fabrication process and accurate match is usually required between the electrical characteristics of memory cell and nonlinear access device, the first three methods are not advisable for most cases.…”
Section: Introductionmentioning
confidence: 99%
“…A third class of switching, related to bipolar, is termed complementary resistive switching (CRS). Originally proposed as a mechanism occurring in devices in which two resistive switching devices are stacked in an antiseries configuration (conceptually similar to two back-to-back diodes in series) [28,29], more recent reports have demonstrated its existence in single switching layers [30][31][32][33]. In this scheme, in the case of a single layer, a device is initially set into a low resistance state at a threshold voltage V th with no current compliance limit applied.…”
Section: Phenomenology Of Filamentary Resistive Switchingmentioning
confidence: 99%